Influence of errors in an estimation of control parameters in an artificial kidney eqipment on the ef-fective value of hemodialysis index dose - Бойко, І.Ф.; Поліщук, С.Т. (Proceedings of National Aviation University (archive), 2004)
The possible reasons in a disagreement of scientists in an estimation of optimum value of haemodialysis index dose are analyzed. It is proved, that the modern mathematical models used for calculation the haemodialysis index dose, can decrease its real value by 20–30 % that can result in ambiguity of compared results.